Intellectual Property Rights and Gastronomy for Traditional Cuisine Tourism in Yogyakarta - Ramadhan, Galih Dwi (ASEAN Journal on Hospitality and Tourism, 2025)
Intellectual Property Rights (IPR) offer critical legal protection for human creations. While gastronomy explores the link between culture and cuisine, the intersection of IPR protection and traditional cuisine tourism remains underexplored in legal scholarship, creating a significant research gap. This paper investigates how IPR can be leveraged to promote traditional cuisine tourism in the Special Region of Yogyakarta. Employing a normative legal research method with statutory and conceptual approaches, the analysis reveals that while traditional cuisine is not directly protectable, specific elements such as unique preparation methods, branding, and commercial practices derived from culinary heritage are eligible for IPR protection by individuals, entities, or communities. The research contributes a legal framework demonstrating how these protections can be strategically owned and utilized to ensure the sustainable development and authenticity of traditional cuisine tourism in Yogyakarta.